JOB LIFE QUALITY AND MOTIVATION FACTORS IN HEALTHCARE - Imran Aslan (eScience Humanity Journal, 2020)
To have a high motivation and better life standards, work life is an important factor It is expected that not just monetary benefits increase the motivation but physiological factor like approval and feeling of helping others. The purpose of this study is determining preferences of job life quality and motivation of workers in healthcare. To determine the Job Quality of Life and motivating factor affecting satisfaction, 109 questionnaires about 10% of staffs (900 staffs) were applied to the Bingöl city main government hospital at third quarter of 2016. Descriptive statistics are used to analyze questionnaires. Materialistic prizes such as permission and wage increase are seen the most effective rewarding methods. Moreover, they do not want to have a good communication with management and they are not eager to take more responsibilities and authority.